N-terminal truncation of STAT1 transcription factor causes CD3- and CD20-negative non-Hodgkin lymphoma through upregulation of STAT3-mediated oncogenic functions - Sana Mumtaz Sheikh; Julia Staab; Martina Bleyer; Aleksandar Ivetic; Fred Lühder; Oliver Wirths; Thomas Meyer (Cell Communication and Signaling)
Abstract The cytokine-driven transcription factor STAT1 (signal transducer and activator of transcription 1) executes anti-microbial and pro-apoptotic functions, and loss-of-function mutations are associated with increased susceptibility to various infections and the development of tumors. A targeted mutation in mice expressing an N-terminally truncated STAT1 protein (STAT1-ΔN) typically develops splenomegaly in animals older than 6 months due to the formation of splenic non-Hodgkin lymphomas. The expression of the STAT1-ΔN variant resulted in the disruption of normal spleen architecture by malignant CD3- and CD20-negative tumor cells, which stained positively for both tyrosine-phosphorylated STAT1 and STAT3. Immunoblotting of lysates from isolated tumor cells revealed the cytokine-independent hyperphosphorylation of both STAT proteins, whereas the expression level of NF-κB was significantly reduced. Gel-shift assays showed that the DNA-binding activity of STAT1-ΔN was increased compared to the wild-type protein. This elevated level of tyrosine-phosphorylated STAT1-ΔN did not further increase upon stimulation of isolated tumor cells with either interferon-γ (IFNγ), lipopolysaccharide (LPS), or the combination of both. Since the truncation mutant was unable to accumulate in the nucleus upon cytokine stimulation, real-time PCR data from tumor tissue as well as from isolated, IFNγ/LPS-treated lymphoma cells demonstrated significantly reduced STAT1-regulated target gene expression despite its observed hyperphosphorylation. The nuclear import defect of tyrosine-phosphorylated STAT1-ΔN was associated with an elevated tyrosine-phosphorylation level of its antagonistic homolog STAT3, which is a known oncogene. These data demonstrate that the lack of STAT1 nuclear accumulation interferes with the functional balance between the two STAT proteins and, thereby, promotes the formation of phospho-STAT3-expressing CD3-/- CD20-/- non-Hodgkin lymphomas in the spleens of the diseased animals.